PHOTOLUMINESCENCE AND CONCENTRATION QUENCHING OF Pr3+ DOPED BaTa2O6 PHOSPHOR - (:unkn) unknown (CROATIAN METALLURGICAL SOC, 2015)
The pure and Pr3+ doped TTB-BaTa2O6 phosphors were obtained by the solid state reaction method at 1 425 degrees C for 20 hours. X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analyses confirmed a single phase of BaTa2O6 up to 10 mol % Pr2O3. SEM analysis also shows that BaTa2O6 grain size decreased with the increasing Pr2O3 concentration. The chemical composition of Pr3+ doped BaTa2O6 structures was confirmed by Energy Dispersive Spectroscopy (EDS) analysis. BaTa2O6:Pr3+ phosphors exhibited on a strong red emission at 620,9 nm, a green emission at 548,3 nm and a red emission at 655,2 nm. Emission intensity increased with Pr3+ doping concentration up to 1,5 mol %, then decreased due to concentration quenching.
Keywords: BaTa2O6; TTB; Pr3+; phosphors; solid state reaction; ENERGY-TRANSFER; IONS